Efektivitas Bokashi Eceng Gondok untuk Meningkatkan Produksi Pada Budidaya Tanaman Sawi (Brassica Juncea L.) di Kecamatan Secanggang Kabupaten Langkat Sumatera Utara - Mutia Ramadhani; Elrisa Ramadhani; Irwan Agusnu Putra (JURNAL AGROPLASMA, 2026)
This study aimed to analyze the effectiveness of water hyacinth bokashi on the growth and yield of mustard plants (Brassica juncea L.) to increase production in Secanggang District, Langkat Regency, North Sumatra. The research was conducted from March to May 2026 using a non-factorial Randomized Block Design (RBD) with five treatments and five replications. The treatments consisted of 0 Ton/ha (control), 5 ton/ha, 10 tons/ha,15 tons/ha, and 20 tons/ha. The observed parameters included plant height, number of leaves, and fresh weight. Data were analyzed using Analysis of Variance (ANOVA) followed by Duncan Multiple Range Test (DMRT) at a 5% significance level. The results showed that the application of water hyacinth bokashi significantly affected the growth and yield of mustard plants. Treatment 20 tons/ha or 30 g/polybag produced the best results in all observed parameters, with the highest plant height of 33.11 cm, the highest number of leaves of 11.20 leaves, and the highest fresh weight of 184.00 g/plant. Therefore, water hyacinth bokashi has the potential to be an effective and environmentally friendly alternative organic fertilizer for increasing mustard plant production.  Keywords: plant biomass, organic bokashi, water hyacinth, vegetative growth, organic fertilizer